2020
DOI: 10.1021/acs.langmuir.0c00007
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Vesicles Self-assembled Directly from an Amphiphilic Europium Complex in an Ionic Liquid

Abstract: Novel luminescent vesicles with enhanced emission were successfully achieved for the first time by an amphiphilic europium complex through its spontaneously self-assembly in an ionic liquid, 1-butyl-3-methylimidazolium hexafluorophosphate ([Bmim]­PF6). The complex was prepared by europium ions coordinated with terpyridine ligands, which were modified with the hydrophilic ethoxy chains. The enhanced absolute quantum yield and prolonged fluorescence lifetime of complex in vesicles were observed because of the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…There have been several reports published in those directions, focusing on both fundamental understanding and applications, oriented towards the nuclear industry. 3,[15][16][17][18][19][20][21][22][23][24] However, due to the limitations of ionic liquids, which pertain to their environmental friendliness, biodegradability, high cost, and toxicity, research associated with metal ion EDDC has not achieved long-lasting success. Therefore, researchers started looking for similar studies with DES.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports published in those directions, focusing on both fundamental understanding and applications, oriented towards the nuclear industry. 3,[15][16][17][18][19][20][21][22][23][24] However, due to the limitations of ionic liquids, which pertain to their environmental friendliness, biodegradability, high cost, and toxicity, research associated with metal ion EDDC has not achieved long-lasting success. Therefore, researchers started looking for similar studies with DES.…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports on designing self-assemblies of lanthanide complexes in the literature. , For simple imaging entities, Rao et al, Ye et al, and Meade et al, respectively, have reported smart in vitro enzymatic reaction-based self-assembling MRI contrast agent, an in vivo self-aggregating fluorogenic small-molecule MR/NIR imaging probe, and a self-assembling AIEgen-Gd/DOTA-peptide-based bimodal luminescence-MRI contrast agent . There have also been literature reports on using Gd-complexes to develop theranostic prodrugs: Shen et al documented a novel MRI theranostic in vivo prodrug self-assembled from small amphiphilic Gd/DTPA-CPT conjugates ( i.e ., acyclic ligand), but their cancer cell selectivity is unknown .…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports on designing self-assemblies of lanthanide complexes in the literature. 7,8 9 an in vivo self-aggregating fluorogenic small-molecule MR/NIR imaging probe, 10 and a self-assembling AIEgen-Gd/DOTA-peptide-based bimodal luminescence-MRI contrast agent. 11 There have also been literature reports on using Gd-complexes to develop theranostic prodrugs: Shen et al documented a novel MRI theranostic in vivo prodrug self-assembled from small amphiphilic Gd/DTPA-CPT conjugates (i.e., acyclic ligand), but their cancer cell selectivity is unknown.…”
Section: ■ Introductionmentioning
confidence: 99%